Perfil de reposta imunológica em lactentes: uso no diagnóstico, prognóstico e monitoração pós-terapêutica da toxoplasmose congênita - Araújo, Thádia Evelyn de (2021)
The early diagnosis of congenital toxoplasmosis (CT) represents an important public health challenge. The search for complementary laboratory indicators for an early and more sensitive diagnosis of congenital infection has been considered relevant to contribute to clinical decision-making and immediate initiation of treatment, which reduces further complications. In addition, several studies have addressed different types of immune response, for a better understanding of how the infected organism responds to the presence of T. gondii. Thus, the present work had two objectives: (i) to perform an integrative analysis of immunological parameters in the identification of complementary biomarkers for the early diagnosis of CT in infants; and (ii) assess the impact of early etiological treatment on the profile of cellular and molecular biomarkers in CT. Using small volumes of whole blood samples, the performance of serum soluble mediators, ex vivo phenotypes of circulating leukocytes and intracellular cytokine profiles upon short-term in vitro stimuli were evaluated as single or combined stepwise biomarker platforms. Results showed that ex vivo serum levels of CXCL9, and the frequencies of circulating CD4+CD25+ T-cells and T. gondii-specific IFN-γ+CD4+ T-cells measured 30-45 days after birth presented high accuracy to distinguish T. gondii-infected infants from healthy age-matched controls (Global Accuracy/AUC = 0.9; 0.9 and 0.8, respectively). Of note was the enhanced performance (Accuracy = 96%) achieved by using a combined stepwise analysis of CD4+CD25+ T-cells and CXCL9. In addition, high global accuracy (AUC = 0.9) with elevated sensitivity (Se = 98%) was also reached by using the total frequency of in vitro IFN-γ-producing T. gondii-specific T-cells (∑ IFN-γ+ CD4+ & CD8+) as a biomarker of congenital toxoplasmosis. Furthermore, the analysis of in vitro T. gondii-specific IL5+CD4+ T-cells and IFN-γ+ NK-cells displayed a high accuracy for early prognosis of ocular lesion in infant with CT (Global Accuracy/AUC = 0.8 and 0.9, respectively). Together, these findings support the relevance of employing the elements of the cell-mediated immune response as biomarkers with potential to endorse early diagnosis and prognosis of congenital ocular toxoplasmosis to contribute for a precise clinical management and effective therapeutic intervention. Regarding the second objective, changes in immune response of children with congenital toxoplasmosis (CT) regarding infection evolution and therapeutic intervention was addressed. Infants with CT presented increased counts of monocytes, CD3-CD16-CD56High, CD3+CD56+ and CD4+ T-cells 1-year after treatment onset (TOXO1-yearAT). Smaller numbers of CD3-CD16-CD56+ and TCRγδ+ T-cells were specifically observed in infants with retinochoroidal lesions (L(+)). When infants were classified based onthe baseline status, expansion of CD3-CD16-CD56High and CD4+ T-cells were observed in L(+) who had active, active/cicatricial or cicatricial lesions. Infants who had active or active/cicatricial lesions display augmented numbers of monocytes, CD3-CD16+CD56+, CD3+CD56+, CD8+DR+ and TCRγδ+ T-cells and those with active/cicatricial or cicatricial at baseline displayed increase in CD14+CD64+ monocytes. Moreover, all L(+) had increased IFN-γ+ and IL-10+ CD4+ T-cells, while L(-) had increased ratios of TNF+, IFN-γ+ and IL-4+ NK-cells upon antigen-specific stimulation. Persistent alterations in leukocytes in TOXO1- yearAT suggest long-term sequels in the immune system of infants with CT. Although treatment had a beneficial impact in shifting the retinochoroidal lesion to a cicatricial state, the implementation of an active prenatal screening program to prevent CT transmission is necessary to minimize the long-term impact of this infection in the immune system. In summary, our data suggest that the immune response profile that occurs in newborns and infants with CT may be useful for the search for new diagnostic and prognostic biomarkers, and for post-therapeutic monitoring of treated patients.